Algoritma Penyelesaian Persamaan Fuzzy Non Linear dengan Metode Modifikasi Newton Raphson dan Implementasinya - Wahyu Megarani; Dorrah Aziz; Amanto Amanto; La Zakaria (Jurnal Siger Matematika, 2020)
Non-linear fuzzy equations are mathematical problems that can be solved. Non-linear fuzzy equations can be solved by numerical methods, namely the Newton Raphson modification method. The Newton Raphson modification method is shown in an algorithm to be implemented with a computer program using the Matlab application. So that the calculation process can be done easily and in a short time. In the non-linear fuzzy equation of a given case, a solution can be found efficiently using the given algorithm.